KLF4 Promotes Diabetic Chronic Wound Healing by Suppressing Th17 Cell Differentiation in an MDSC-Dependent Manner. (15th September 2021) - Yang, Xiong; Mathis, Bryan J.; Huang, Yu; Li, Wencheng; Shi, Ying
Abstract : Objectives . Diabetic wound inflammation deficiencies lead to ulcer development and eventual amputation and disability. Our previous research demonstrates that myeloid-derived suppressor cells (MDSCs) accumulate during inflammation and promote chronic wound healing via the regulation of Kruppel-like factor 4 (KLF4). In this study, we aimed to investigate the potential roles of MDSCs and KLF4 in diabetic wound healing. Methods . An ob/ob mouse pressure ulcer (PU) model was used to evaluate the process of wound healing. The expression levels of KLF4 and IL-17A were measured by real-time PCR, and the population of MDSCs and Th17 cells was measured by flow cytometry. The levels of cytokines were determined by an immunosuppression assay. Results . KLF4 deficiency in the diabetic PU model resulted in decreased accumulation of MDSCs, increased expansion of Th17 cells, and significantly delayed wound healing. Conversely, KLF4 activation by APTO-253 accelerated wound healing accompanied by increased MDSC populations and decreased numbers of Th17 cells. MDSCs have been proven to mediate Th17 differentiation via cytokines, and our in vitro data showed that elevated KLF4 expression in MDSCs resulted in reduced Th17 cell numbers and, thus, decreased levels of cytokines indispensable for Th17 differentiation. Conclusions . Our study revealed a previously unreported function of KLF4-regulated MDSCs in diabetic wound healing and identified APTO-253 as a potential agent to improve the healing of pressure ulcers.